Determinants of Economic Growth in Lower-Middle and Upper-Middle Income Asean Countries: The Role of Foreign Debt, Foreign Capital Investment, Trade Openness, Labor, and Government Expenditure - Nurushofiah, Iin; Iskandar, Deden Dinar (AFEBI Economic and Finance Review, 2024)
This research aims to determine the influence of foreign debt, foreign investment, trade openness, labor, and government expenditure on economic growth in ASEAN middle to lower-middle-income countries from 2000-2019. This research uses panel data with secondary data obtained from reports published by the World Bank and the Malaysian Authority. The analytical model used in this research is a multiple linear regression model equipped with the help of the Eviews 10 program. To see the influence of the independent variable on the dependent variable, the best estimation model was chosen, namely the fixed effect model (FEM). The results of this research show that foreign debt, foreign investment, trade openness, labor, and government expenditure simultaneously have a significant influence on the economic growth of ASEAN lower-middle-income countries in 2000-2019. Meanwhile, partially it shows that the foreign debt variable has a negative but not significant effect on the economic growth of ASEAN lower middle - upper middle-income countries. The variables of foreign investment, labor, and government expenditure have a positive and significant effect on the economic growth of lower-middle and upper-middle-income ASEAN countries. Meanwhile, the trade openness variable has a positive but not significant effect on economic growth in ASEAN lower middle - upper-middle-income countries.